Choral Constructions in Greek Culture : The Idea of the Chorus in the Poetry, Art and Social Practices of the Archaic and Early Classical Period - Steiner, Deborah Tarn (Cambridge University Press, 2021)
Cover -- Half-title page -- Title page -- Copyright page -- Dedication -- Contents -- List of Illustrations -- Preface and Acknowledgements -- Introduction: τί δεῖ με χορεύειν -- -- 1 Choreia at the Forge: Tripod Cauldrons, Golden Maidens and the Choral Dancers on Achilles' Shield in Iliad 18 -- 2 From the Demonic to the Divine: Gorgons, Cauldrons and Choral Dance -- 3 Flying with the Birds: Avian Choreia and Bird Choruses in Art and Text -- 4 The Carnival of the Animals: Dancing in Herds -- 5 Water Music: Nymphs, Ships and Choral Aquatics -- 6 A Chorus of Columns: Pindar's Agalmata and the Architectural Chorus -- 7 Choral Fabrications: Weaving, Cloth-Making and Choral Song and Dance -- 8 Choreo-graphy: Choreia and Alphabetic Writing -- 9 Girls in Lines: Catalogues and Choruses -- 10 Choral Envisioning: Archaic and Early Classical Choral Lyric and Post-Classical Accounts of Enargeia -- Bibliography -- Index Locorum -- Subject Index.